Circulating miR-1826 in plasma correlates with circulating tumor cells and is a prognostic marker in colorectal cancer - Zhihua Xu; Tianyi Xi; Ye Han; Xiaobo Guo; Fei Liu; Min Jiang; Daiwei Wan; Xiaofeng Xue; Songbing He; Rui Ren; Wei Li; Qiaoming Zhi (Tumor Biology)
Our previous study showed that miR-1826 was a newly identified oncogenic non-coding RNA in colorectal cancer. But the potential relationship between miR-1826 and tumor metastasis has not been fully elucidated. The purpose of this study was to evaluate the clinical significance of circulating miR-1826 and its possible associations with circulating tumor cells in colorectal cancer. Our results first found that serum miR-1826 was significantly upregulated in colorectal cancer patients, compared with that in healthy volunteers ( p = 0.003). Similar results were also found in colorectal cancer with distant metastasis ( p = 0.001) and advanced colorectal cancer ( p < 0.001) patients, respectively. Clinicopathological analysis implied that circulating miR-1826 was positively associated with pT stage ( p = 0.026), lymphatic metastasis ( p = 0.034), distant metastasis ( p = 0.012), and tumor–node–metastasis stage ( p = 0.020). Besides, our univariate and multivariate analyses demonstrated that high serum miR-1826 expression could act as a prognostic and independent factor for overall survival of colorectal cancer patients ( p < 0.05), which led to a poorer 5-year overall survival rate ( p = 0.025). The area under the curve value of circulating miR-1826 was up to 0.848 ± 0.043, which strongly suggested serum miR-1826 as an effective diagnostic biomarker in colorectal cancer patients ( p < 0.001). Our subsequent experiments demonstrated that patients with high level of circulating tumor cells showed a higher level of miR-1826 expression, compared with the circulating tumor cell–negative patients ( p = 0.011). Similar results also showed that the amount of circulating tumor cells in high miR-1826 group was significantly higher than that in low miR-1826 group ( p = 0.001). Furthermore, the relationship between serum miR-1826 and circulating tumor cells was analyzed using SPSS software and a significant logarithmic relationship was found, which meant that circulating miR-1826 closely correlated with the amount of circulating tumor cells in colorectal cancer patient serum ( r = 0.283, p < 0.01). Our findings strongly suggested that serum miR-1826 could serve as an effective and non-invasive biomarker for diagnosis and prognosis of colorectal cancer. Circulating miR-1826 may be an important target in colorectal cancer therapy.